Induction Strategy for Locally Advanced Thymoma - Zhang, Yang; Li, Zongjuan; Chen, Yixing; Tan, Lijie; Zeng, Zhaochong; Ding, Jianyong; Du, Shisuo (Frontiers in Oncology, 2021)
Surgery remains cornerstone for the management of thymoma. Complete surgical resection (R0), is recognized as the constant and significant factor for prognosis. However, in locally advanced (Masaoka-Koga stages III-IVa) thymomas, achieving R0 resection remains challenging due to local-regional invasion of the disease. Induction treatment, with the aim of reducing bulky tumor mass, offers new strategy to facilitate totally surgical resection. Herein, we reviewed recent progress and provided a comprehensive overview of induction strategy in locally advance thymoma.